Analisis Kepatuhan Atas Penerapan Internet Corporate Reporting (ICR) pada Bank Umum Syariah Di Indonesia - Dessy Noor Farida (ITB AAS INDONESIA Surakarta, 2019)
In the digital business era, having a high-quality and effective website is one of the priority strategies for many companies. Companies that have information on the company's website can make it easier for users to find all the necessary information related to the company without incurring high costs. With corporate reporting, the company will present financial information in a timely manner to convince users of financial statements that the data available is relevant information. In order to increase transparency while increasing the access of shareholders and other stakeholders to the information of issuers or public companies OJK (Otoritas Jasa Keuangan) issues regulations related to the website of the issuer or public company. The results of this study indicate that Islamic banks have not utilized the facilities provided on the website optimally. This is indicated by the ICR index average of Islamic banks which is still in the range of 51.1. The highest ICR index is owned by Bank Muamalat Indonesia with a score of 73.97 and the lowest ICR index is owned by Bank Mega Syariah bank with a score of 36.99.